The History and Context of the Brno Ring Boulevard - Adam Guzdek (Architektúra & Urbanizmus)
Frequently compared to Vienna’s Ringstrasse, the Brno ring boulevard must nonetheless – despite the shared association with Ludwig Förster – be considered a completely unique urban development, dating to the end of the 18th century. Competition proposals for the design of the Brno ring boulevard predetermined the final form of the regulatory plan, which was used for the the curving boulevards constructed between 1863 and 1885. Although it might appear that Brno’s ‘ring’ was already complete in the 19th century, the 20th century was the time to see the greatest architectural change. The story of the ring boulevard began with Napoleon, and even after 200 years, its development is ongoing.